Vegetative propagation of rootstocks and budding of ‘Irati’ Japanese plum in recently rooted softwood cuttings - Nicolao, Guilherme; Lackman, Karen Pinheiro; Mayer, Newton Alex; Bianchi, Valmor João (Revista de Ciências Agroveterinárias, 2022)
In Brazil, nursery plum trees are traditionally produced by interspecific budding, where the rootstock is propagated by peach seeds often obtained from the waste of peach industrialization, which promotes heterogeneity among rootstocks. In addition, the conventional system of nursery plum tree production under field conditions requires approximately 18 months, from taking seeds to selling grafted trees. This research has aimed to assess the technical feasibility of adventitious root formation in the softwood cuttings of six cultivars of Prunus spp., as well as the budding of ‘Irati’ plum in the recently rooted softwood cuttings developed in a greenhouse, in order to reduce the time required to produce nursery plum trees with cloned rootstocks. Two tests were carried out in a greenhouse involving the rootstock propagation step (1) and the ‘Irati’ plum budding on the recently rooted cuttings (2). Under the experimental conditions adopted, we have concluded that it is technically feasible to propagate the cultivars of Prunus spp. under an intermittent mist system with 22 cm-long softwood cuttings. The cultivars ‘Genovesa’, ‘Marianna 2624’, and ‘Myrobalan 29C’ showed good propagation ability with high percentage of live rooted cuttings (>90%) and low mortality in acclimation (≤5.0%). On the other hand, the budding of the ‘Irati’ plum by the chip budding method made in April in the original rootstock cutting showed low percentages of success (between 17.1% and 31.4%) and the beginning of scion growth was only observed at the end of winter. Considering the time necessary for the softwood cutting to root and the satisfactory growth of the scion for planting the nursery trees at the appropriate time (winter), we could not produce budded nursery trees of ‘Irati’ plum in less than 12 months, counting from the cuttings made.